THE APPLICATION OF MONTREAL 1999 CONVENTION TO CLAIM COMPENSATION ON FLIGHT DISRUPTION - Kautsar, Izzy Al; Fitriyanti, Fadia (Kertha Semaya : Journal Ilmu Hukum; Vol 8 No 7 (2020), 2020)
The purpose of this article aims to analyze the application of the montreal 1999 convention and responbsibility of airlanes company  to the flight accidents. This article uses a case study approach and normative juridical approach, This normative research used secondary data consisting of primary, secondary, and tertiary legal materials.. The research describes the posisition of montreal 1999 convention based on Indonesian regulation and the extent of responbsibility of airlanes company  to the flight accidents. The results of this article show that, include liabilities arising in case of an air accident by the airline concerned, which are, indicate that the application of the montreal 1999 convention is able to guarantee the rights of consumers, who feel disadvantaged by accidents, also the liability of airlanes in flight disruption depends on the consequences experienced of the goods and victims. Suggestions from researchers that the government should focus on cooperating airlines as well as a bridge to the victims in solving problems relating to the compensation.